Common Fixed Point Theorems for Conversely Commuting Mappings Using Implicit Relations. (8th December 2013) - Chauhan, Sunny; Sahper, Huma
Abstract : The object of this paper is to utilize the notion of conversely commuting mappings due to Lü (2002) and prove some common fixed point theorems in Menger spaces via implicit relations. We give some examples which demonstrate the validity of the hypotheses and degree of generality of our main results.